PELATIHAN PEMANFAATAN ALAT PERAGA PEMBELAJARAN MATEMATIKA BAGI GURU SEKOLAH DASAR - Rahmatya Nurmeidina; Iin Ariyanti (STKIP PGRI Sidoarjo, 2019)
The use of media for teaching is important in mathematics learning in order to make learning more meaningful and students can easily understand mathematical concepts. Therefore, the purpose of this activity is to provide insight and skills to elementary school teachers so that they have expertise in the use of mathematics media for teaching, such as integer coins, multiplication houses and KPK and FPB boards. This activity was attended by teachers at Tamban Muara 1 Elementary School . The results of this activity were adding insight, increasing teacher motivation and improving teacher skills in using mathematics media for teaching.